Workshop on Enhancing Elementary School Teachers' Competency in Interactive Digital Learning Through The Use of Smartphone-Based Digital Platforms: Workshop Peningkatan Kompetensi Guru Sekolah Dasar dalam Pembelajaran Digital Interaktif melalui Pemanfaatan Platform Digital Berbasis Smartphone - Aan Yuliyanto; Candra Tri Utami; Tia Citra Bayuni; Natasya Natasya; Julia Anis Handayani; Rosafina Irene; Siti Nurholisoh Dewi; Muhammad Hilman Falahuddin Assadam; Ummu Nizwah (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract This workshop aims to improve the competence of elementary school teachers using digital learning media, in particular, Wordwall, Pickerwhell and Ahaslides. This activity is a Community Service Program of the Elementary School Teacher Education Lecturer Team of Universitas Pelita Bangsa which was carried out online involving 2 Principals, 15 Elementary School Teachers, and 79 Students spread across regions in Indonesia, especially Bekasi, West Java. The workshop was carried out through three stages, namely preparation, material delivery, and evaluation. In the preparation stage, the service team prepared an online workshop by inviting the cooperation of several schools and involving students. In the implementation stage, workshop participants participated in the presentation of theory and practice in the use of digital platforms through Zoom Meetings and then the evaluation was carried out through the help of Google Form after the implementation. The results of the evaluation showed that 82% of participants gave a very useful, solution, and innovative assessment of the implementation of the workshop, while 56.1% of participants rated YouTube as the easiest platform to use, followed by Wordwall at 34.1%. Overall, this workshop received an average satisfaction of 4.88 out of 5. Thus, this digital learning workshop is effective in improving teachers' competence in smartphone-based digital learning. It is hoped that there will be no more limitations for teachers to implement digital learning by utilizing gadgets owned by all groups, namely smartphones. Keywords: Workshop; Digital Learning; Elementary School Teachers; Smartphone Abstrak Workshop ini bertujuan meningkatkan kompetensi Guru SD memanfaatkan media pembelajaran digital, khususnya, Wordwall, Pickerwhell dan Ahaslides. Kegiatan ini merupakan Program Pengabdian Masyarakat Tim Dosen Pendidikan Guru Sekolah Dasar Universitas Pelita Bangsa yang dilaksanakan secara daring dengan melibatkan 2 Kepala Sekolah, 15 Guru SD, dan 79 Mahasiswa yang tersebar di wilayah di Indonesia khususnya Bekasi, Jawa Barat. Workshop dilaksanakan melalui tiga tahapan, yaitu persiapan, penyampaian materi, dan evaluasi. Pada tahap persiapan tim pengabdian mempersiapkan workshop secara daring dengan mengajak kerjasama beberapa sekolah dan melibatkan mahasiswa. Tahap implementasi, peserta workshop mengikuti pemaparan teori dan praktik dalam penggunaan platform digital melalui Zoom Meeting kemudian pada evaluasi dilaksanakan melalui bantuan Google Form usai pelaksanaan. Hasil evaluasi menunjukkan 82% peserta memberikan penilaian sangat Bermanfaat, Solutif, dan Inovatif terhadap pelaksanan workshop, sementara 56,1% peserta menilai YouTube sebagai platform yang paling mudah digunakan dan disusul Wordwall 34,1%. Keseluruhan, workshop ini mendapatkan rata-rata kepuasan 4,88 dari 5. Dengan demikian workshop pembelajaran digital ini efektif meningkatkan kompetensi guru dalam pembelajaran digital berbasis smartphone. Diharapkan tidak ada lagi keterbatasan guru mengimplementasikan pembelajaran digital dengan memanfaatkan gawai yang dimiliki semua kalangan yaitu Smartphone. Kata kunci: Workshop; Pembelajaran Digital;Guru SD; Smartphone